2023
DOI: 10.1021/acs.jmedchem.3c00724
|View full text |Cite
|
Sign up to set email alerts
|

Diamino Allose Phosphates: Novel, Potent, and Highly Stable Toll-like Receptor 4 Agonists

Juhienah K. Khalaf,
Laura S. Bess,
Lois M. Walsh
et al.

Abstract: Most known synthetic toll-like receptor 4 (TLR4) agonists are carbohydratebased lipid-A mimetics containing several fatty acyl chains, including a labile 3-O-acyl chain linked to the C-3 position of the non-reducing sugar known to undergo cleavage impacting stability and resulting in loss of activity. To overcome this inherent instability, we rationally designed a new class of chemically more stable synthetic TLR4 ligands that elicit robust innate and adaptive immune responses. This new class utilized a diamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Previous studies identified the importance of lipopolysaccharide (LPS) engagement of TLR4 in the clearance of Pa infections [ 21 ], and thus we hypothesized that the use of a TLR4 agonist would enhance an antibody response specific to CoaB. A component of LPS, Lipid A, is the bioactive element and is the structural basis of our synthetic TLR4 agonist, INI-2002 ( Figure 1 E) [ 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified the importance of lipopolysaccharide (LPS) engagement of TLR4 in the clearance of Pa infections [ 21 ], and thus we hypothesized that the use of a TLR4 agonist would enhance an antibody response specific to CoaB. A component of LPS, Lipid A, is the bioactive element and is the structural basis of our synthetic TLR4 agonist, INI-2002 ( Figure 1 E) [ 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvants bound to PRRs can result in the production of specific cytokines and cell-surface proteins, which can enhance adaptive immunity when co-administered with an antigen [ 12 ]. The lead adjuvant described herein, INI-2002, is a synthetic TLR4 agonist that enhances both cell-mediated and humoral immunity [ 13 ]. Animals vaccinated with the CoaB peptide conjugated to CRM197 and adjuvanted with INI-2002 had increased antigen-specific antibody production when compared to animals vaccinated with the CoaB conjugate adsorbed to Alhydrogel.…”
Section: Introductionmentioning
confidence: 99%